Edukasi: Waspada Jebakan Pinjaman Online Ilegal - Rusli, Devvy; Chusnah, Flourien Nurul; Supriati, Diana; Sulistyowati (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
Online loans circulating in society provide easy and fast access to funds. However, this convenience is often accompanied by high interest rates, additional fees, and unfair debt collection practices. This community service activity aims to educate the public about legal and illegal online loans, which are increasingly widespread. The service was conducted using a counseling approach, beginning with an initial identification through short questions to assess participants’ knowledge and experiences related to online loans. This was followed by a presentation on the characteristics of illegal online loans based on the criteria issued by the Financial Services Authority (OJK), and concluded with a question-and-answer session. The community service activity was held on Thursday, June 29, 2025, in Rawamangun Village, Pulogadung District, East Jakarta. Based on the results of the discussion and question-and-answer session, it can be concluded that participants were able to distinguish between legal and illegal online loans, understood preventive measures and reporting mechanisms for illegal online loans, and demonstrated improved financial literacy in making loan-related decisions.